Pemetaan Struktur Media Sosial Pemerintah Daerah Dalam Mencapai Akuntabilitas Publik - Priyambodo, Victoria Kusumaningtyas; Lestari, Baiq Anggun Hilendri; Sukma, Paradisa; Awaliah, Azizah; Hairuzzami, Baiq Arnita (Universitas Negeri Padang, 2024)
In the modern world, social media as a means of information sharing, communication and interaction is increasingly popular and government administrations are actively taking advantage the dominance of social media to promote public goals. Citizen participation is expected to improve the effectiveness and responsiveness of the government. This also promotes the creation of public accountability. One way to conceptualize and measure social media engagement is to map the flow of information between government agencies and the public. This research aims to identify and map the communication structure and involvement of local government with the community to improve the public accountability process. The data collection method used in this research is content analysis with a structured framework. Based on observations of 38 Provincial Governments accounts, on four social media (Facebook, X/Twitter, Instagram and YouTube), the structure of public involvement is still dominant in the one-to-many communication model. Local Government actively provides one-way information without responding to user comments or questions.